Optimal Anticoagulation for Pregnant Women with Mechanical Heart Valves - D'Souza, Rohan; Silversides, Candice K.; McLintock, Claire (Seminars in Thrombosis and Hemostasis, 2016)
The prothrombotic state of pregnancy increases the risk of thromboembolic complications and death in women with mechanical heart valves (MHVs). Although it is accepted that these women must be on therapeutic anticoagulation throughout pregnancy, competing maternal and fetal risks, as well as the lack of high-quality data from prospective studies, make the choice of the optimal method of anticoagulation challenging. Vitamin K antagonists (VKAs) are associated with fewer maternal complications, but conversely also the lowest live birth rates as well as warfarin-related embryopathy and fetopathy. Low-molecular-weight heparin (LMWH) does not cross the placenta and is associated with fewer fetal risks but more maternal complications. Sequential treatment involving VKAs in the second and third trimesters and either low-molecular-weight or unfractionated heparin in the first trimester, although appealing is still associated with maternal complications, especially around the time of bridging. As absolute equipoise of maternal versus fetal wellbeing is unlikely, patient preferences should be considered in decision making. A multidisciplinary team including hematologists, cardiologists, obstetric physicians, and high-risk obstetricians with expertise in the management of pregnant women with cardiac disease is required to optimize outcomes. Prospective studies are needed to determine the anticoagulant regimen for women with MHVs that provides optimal and acceptable maternal and fetal outcomes.
Keywords: anticoagulation; pregnancy; mechanical heart valves